Penerapan K-Means Clustering Pada Klasifikasi Risiko Kesehatan Ibu Hamil - Nurtiani, Ni Made Novia; Astawa, I Gede Santi (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p48, 2022)
The health condition of pregnant women greatly affects the growth and development of the fetus in the womb. There are many cases of maternal and infant deaths that occur in the world. Both caused by the condition of the mother's health during pregnancy and after childbirth. Several factors affect the health condition of pregnant women, namely age, blood pressure, blood sugar levels in the body of pregnant women, body temperature of pregnant women. This study will apply the K-Means method to classify the health risks of pregnant women. The author will also use the Elbow method to find the right cluster to classify.